2022
DOI: 10.3390/ijerph191811364
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge, Dietary Habits, and Food Labels Use—A Representative Cross-Sectional Survey among Adults in Poland

Abstract: An unhealthy diet is an important risk factor for disability and premature death. This study aimed to assess nutrition knowledge, dietary habits, and food label use among adults in Poland as well as to identify factors associated with diet-related behaviors. A cross-sectional survey was carried out in July 2020 on a non-probability quota-based sample of 1070 adult citizens of Poland. The most common sources of nutrition knowledge were news websites (41.8%) or family/friends (32.4%). Over one-quarter of adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Different genders of the study participants showed differences in scores for healthy diet knowledge and healthy diet practice, with females scoring higher than males in both aspects (refer to Table 2 ); this finding was in line with the results from other research [ 38 ]. This finding may have resulted from women being assigned additional responsibilities for cooking and diet decisions in society.…”
Section: Discussionsupporting
confidence: 90%
“…Different genders of the study participants showed differences in scores for healthy diet knowledge and healthy diet practice, with females scoring higher than males in both aspects (refer to Table 2 ); this finding was in line with the results from other research [ 38 ]. This finding may have resulted from women being assigned additional responsibilities for cooking and diet decisions in society.…”
Section: Discussionsupporting
confidence: 90%
“…The minimum age was 18 years old and respondents were randomly sampled from the market. Knowledge in nutrition 35 defines awareness of practices and concepts about health and nutrition. This include knowledge of food groups, food as major sources of nutrients and optimal food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, college students, who were mostly male, are considered a population with high-risk behaviours including unhealthy dietary habits, alcohol drinking, and low physical activity, which adversely affect metabolic risk including insulin sensitivity and lipid profile [30,31]. Furthermore, adverse effects of dietary habits on metabolic risk are especially true in the Polish population consuming a diet high in saturated fat and sugar, with low consumption of polyunsaturated fat and micronutrients [32,33]. Therefore, it cannot be excluded that the present data reflect the effect of ectopic fat depots but also the specific diet and lifestyle of students on metabolic risk.…”
Section: Discussionmentioning
confidence: 99%